Effect of Latex Rubber as Asphalt Additive to the Characteristics of AC-WC Mixture - Sucipto, Prayogi Adi; Utami, Adita; Rahmatunnisa, Syifa Nurhaliza; Saputra, Syawaldi; Brawijaya, Brawijaya (Universitas Tribhuwana Tunggadewi Malang, 2023)
Quality improvement can be achieved by making innovations in the development of rubber asphalt material. This research was conducted to determine the effect of adding natural rubber as an additive to the wear-resistant Laston mixture (AC-WC). This study made 33 total samples, which were divided into 18 conventional asphalt mixtures and 15 rubber asphalt mixtures, with normal asphalt variations ranging from 5.5% - 8% and for rubber with variations of 5% - 7% of optimum asphalt weight, respectively each with an interval (0.5 %). It was mixed using a wet process. Based on the 2018 General Highways Specifications, Optimum Asphalt Content (OAC) was obtained at 7.5% and Optimum Rubber Content (ORC) at 6%. The test results for the stability and melting values of normal asphalt were 1786.22 kg and 3.56 mm, while the tests for the stability and melting values for rubber asphalt were 1181.22 kg and 3.6 mm. It can be interpreted that adding this rubber content increases the stability of the value 2x greater than the point where the stability value falls on the normal asphalt content variation of 8%.